2016
DOI: 10.1111/wbm.12110
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the seed germination and seedling emergence of muskweed (Myagrum perfoliatum)

Abstract: Myagrum perfoliatum is a noxious broad‐leaved weed in western Iranian farming systems. A better understanding of the timing of seedling emergence would facilitate the development of better control strategies for this weed. Therefore, the objective of this study was to examine the effects of different factors on muskweed seed germination. Only 2.8% of the seeds of this species, which are encapsulated in siliques, germinated by, while the seeds that had been removed from the siliques had a 50% germination rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…Germination of both seed types of T. arvensis in the presence or absence of light was the same and was not affected by light. Similar to our results, the insensibility of weed seeds to light for germination (nonphotoblastic) has been reported for many other species, such as Centaurea balsamita Lam (Nosratti et al 2017c), Myagrum perfoliatum (Honarmand et al 2016), Sophora alopecuroides (Nosratti et al 2017a), Solanum ptycanthum Dun (Zhou et al 2005) and Ipomoea purpurea Roth (Singh et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Germination of both seed types of T. arvensis in the presence or absence of light was the same and was not affected by light. Similar to our results, the insensibility of weed seeds to light for germination (nonphotoblastic) has been reported for many other species, such as Centaurea balsamita Lam (Nosratti et al 2017c), Myagrum perfoliatum (Honarmand et al 2016), Sophora alopecuroides (Nosratti et al 2017a), Solanum ptycanthum Dun (Zhou et al 2005) and Ipomoea purpurea Roth (Singh et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…), Myagrum perfoliatum (Honarmand et al . ), Sophora alopecuroides (Nosratti et al . ), Solanum ptycanthum Dun (Zhou et al .…”
Section: Discussionmentioning
confidence: 99%
“…Centaurea iberica was tolerant to water stress, compared to other drought‐tolerant Iranian weeds (Eslami ; Ebrahimi & Eslami ; Honarmand et al . ). Based on this study's results, the dry soils in the western parts of Iran are favorable for the germination of C. iberica .…”
Section: Discussionmentioning
confidence: 97%
“…black nightshade (Solanum nigrum) (Taab and Andersson, 2009), common lambsquarters (Chenopodium album) (Eslami, 2011), eastern black nightshade (S. ptycanthum) , goosegrass (Eleusine indica) (Chauhan and Johnson, 2008), and horseweed (Conyza canadensis) (Nandula et al, 2006). However, light was not required for the germination of hairy nightshade , Japanese brome (Bromus japonicus) (Li et al, 2015), and muskweed (Myagrum perfoliatum) (Honarmand et al, 2016).…”
Section: Effect Of Alternating Temperature and Lightmentioning
confidence: 99%
“…The concentration required for 50% inhibition of maximum germination was 70.6 mM NaCl ( Figure 6A). The maximum concentration at which no seed could germinate for barnyardgrass (Echinochloa crus-galli) (Sadeghloo et al, 2013), citronmelon (Ramirez et al, 2014), Japanese brome (Li et al, 2015), muskweed (Honarmand et al, 2016), and spotted spurge (Asgarpour et al, 2015) was 400, 300, 360, 250, and 160 mM NaCl, respectively. These results showed that velvetleaf is not tolerant to salinity as compared with the above weed species, which could germinate at high NaCl concentration.…”
Section: Effect Of Salinity and Alkalinity Stressmentioning
confidence: 99%